The Effect of Trade Openness and Financial Openness on Economic Growth During the ASEAN Free Trade Area (AFTA) - Ilham Basrian Jasuma Putra; Muhammad Ghafur Wibowo (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2026)
This study aims to determine the effect of trade openness and financial openness on the economic growth of 6 ASEAN countries during the ASEAN Free Trade Area (AFTA) from 1992-2022. This study uses a quantitative method using secondary data from 1992-2021 sourced from the Central Statistics Agency (BPS), World Bank, UN Comtrade Database, and ASEANstats. This study uses panel data analysis with the Fixed Effect Model (FEM) as the chosen model to estimate using Eviews 9. The test results show that trade and financial openness positively and significantly affect the economic growth of 6 ASEAN countries.